Immune and Neuroprotective Effects of Physical Activity on the Brain in Depression - Phillips, Cristy; Fahimi, Atoossa (Frontiers in Neuroscience, 2018)
Physical activity—a lifestyle factor that is associated with immune function, neuroprotection, and energy metabolism—modulates the cellular and molecular processes in the brain that are vital for emotional and cognitive health, collective mechanisms that can go awry in depression. Physical activity optimizes the stress response, neurotransmitter level and function (e.g., serotonergic, noradrenergic, dopaminergic, and glutamatergic), myokine production (e.g., interleukin-6), transcription factor levels and correlates [e.g., peroxisome proliferator-activated receptor C coactivator-1α [PGC-1α], mitochondrial density, nitric oxide pathway activity, Ca2+ signaling, reactive oxygen specie production, and AMP-activated protein kinase [AMPK] activity], kynurenine metabolites, glucose regulation, astrocytic health, and growth factors (e.g., brain-derived neurotrophic factor). Dysregulation of these interrelated processes can effectuate depression, a chronic mental illness that affects millions of individuals worldwide. Although the biogenic amine model has provided some clinical utility in understanding chronic depression, a need remains to better understand the interrelated mechanisms that contribute to immune dysfunction and the means by which various therapeutics mitigate them. Fortunately, convergent evidence suggests that physical activity improves emotional and cognitive function in persons with depression, particularly in those with comorbid inflammation. Accordingly, the aims of this review are to (1) underscore the link between inflammatory correlates and depression, (2) explicate immuno-neuroendocrine foundations, (3) elucidate evidence of neurotransmitter and cytokine crosstalk in depressive pathobiology, (4) determine the immunomodulatory effects of physical activity in depression, (5) examine protocols used to effectuate the positive effects of physical activity in depression, and (6) highlight implications for clinicians and scientists. It is our contention that a deeper understanding of the mechanisms by which inflammation contributes to the pathobiology of depression will translate to novel and more effective treatments, particularly by identifying relevant patient populations that can benefit from immune-based therapies within the context of personalized medicine.